2019
DOI: 10.1080/00343404.2019.1602257
|View full text |Cite
|
Sign up to set email alerts
|

The role of tax havens and offshore financial centres in shaping corporate geographies: an industry sector perspective

Abstract: This paper investigates the role of tax havens and offshore financial centres (THOFC) in the global economy. Network analysis of 24 industry sectors suggests that THOFC feature prominently in knowledge-intensive activities such as pharmaceuticals, biotechnology and semiconductors, and are least significant in industrial activities such as automobiles and consumer durables, and place-bound activities such as real estate and retailing. Contrasting with the notion that most THOFC are 'rogue' offshore territories,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 61 publications
(86 reference statements)
2
25
0
Order By: Relevance
“…The connectivity patterns that emerged from our static analysis of intrafirm relationships provide empirical evidence of the processes of globalization, financialization, and the rise of state capitalism. This has also been found in previous studies on the energy sector to explain the positions of global cities (Goerzen, Asmussen, and Nielsen 2013), energy hubs (Toly et al 2012;, national capitals (Toly et al 2012;Breul 2019), and THOFCs (Sigler et al 2019;Verbeek and Mah 2020) at the core of global oil and gas firm networks.…”
Section: Resultssupporting
confidence: 80%
“…The connectivity patterns that emerged from our static analysis of intrafirm relationships provide empirical evidence of the processes of globalization, financialization, and the rise of state capitalism. This has also been found in previous studies on the energy sector to explain the positions of global cities (Goerzen, Asmussen, and Nielsen 2013), energy hubs (Toly et al 2012;, national capitals (Toly et al 2012;Breul 2019), and THOFCs (Sigler et al 2019;Verbeek and Mah 2020) at the core of global oil and gas firm networks.…”
Section: Resultssupporting
confidence: 80%
“…Singapore, for example, has been shown to be a gateway city in upstream oil and gas global production networks, and has a long history as a refinery and transport and logistics hub for the petrochemical industry (Breul and Diez 2018). Finally, in the territorial configuration of the global petrochemical industry, we identify the reorientation from supply-or demand-side advantages to purely financial considerations, leading to global firm networks mimicking geographies of taxation (Sigler et al 2020). No less than five out of ten top meeting points are often listed as THOFCs: Hong Kong, Singapore, Kuala Lumpur, Amsterdam, and Wilmington (Philadelphia).…”
Section: Results: Interlocking Network In the Petrochemical Industrymentioning
confidence: 93%
“…Finally, THOFCs have also recently been identified as a specific kind of nodes in global firm networks. Sigler et al (2020) showed that the role of place in decisionmaking has partly been reoriented from supply-or demand-side advantages to purely financial considerations, with global firm networks mimicking geographies of taxation.…”
Section: World City Network-spatial Corporate Interlockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consultant territories sit outside of the community of the territories that they mediate for (who are in the same community). It might also be akin to 'round-tripping' in which territories from one community disguise investments back into the community by first routing payments to locations with more attractive tax regimes or regulatory benefits (Fung et al, 2011;Sigler et al, 2019).…”
Section: Author Manuscriptmentioning
confidence: 99%